2014
DOI: 10.13111/2066-8201.2014.6.s1.8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Dynamic Stall Control

Abstract: In this paper we investigated numerically the dynamic stall phenomenon and the possibilities to control it, with application to vertical axis wind turbines (for urban users). The Phenomenon appear at low tip speed ratio (TSR<4) and it has a great impact on structural integrity of the wind turbine and power performances. For this reason we performed a computational study of dynamic stall around NACA 0012 airfoil in pitching motion at relative low Reynolds number (10 5 ). Also, we performed the same analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A 2D CFD model was used to represent the single bladed Darrieus turbine since it is sufficient to reveal the factors influencing the performance and majority of flow physics surrounding the VAWT [9][10][11]. The CFD package Ansys Fluent 15.0 was used for all simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2D CFD model was used to represent the single bladed Darrieus turbine since it is sufficient to reveal the factors influencing the performance and majority of flow physics surrounding the VAWT [9][10][11]. The CFD package Ansys Fluent 15.0 was used for all simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Modifications of turbulence viscosity equation for k-ε based turbulence model was carried out resulting in a significant improvement of DS predictions for low Reynolds number flow. In 2014, Frunzulica et al [9] numerically investigated the dynamic stall phenomenon and the possibility to control it, with the application to urban VAWTs. The results showed that SST and Trans-SST k-ω turbulence models predicted the experimental data with a good accuracy in the upstroke phase.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting airfoil stalling dynamics using numerical solutions [ 21 ], combining pitch-plunge oscillations of an airfoil for power production [ 14 ], dynamic stall control by airfoil deformation [ 22 ], and studying the noise produced on an oscillating airfoil [ 23 ] all contribute to the potential applications of dynamic stall in both research and industrial contexts. The main focus regarding recent dynamic stall investigations is placed on rotating wings with helicopter applications [ 24 , 25 ] and vertical axis wind turbine applications [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques can be divided based on energy expenditure into passive and active flow control techniques. Several active flow control devices, such as the leading-edge rod, leading-edge slot blowing [ 12 ], the blowing jet [ 13 ], the oscillating flap [ 14 ], the synthetic jet [ 15 , 16 ], and dielectric barrier discharge plasma actuators [ 17 ] have been developed and investigated. In general, dynamic stalls can be suppressed using active flow control techniques by modifying the control settings.…”
Section: Introductionmentioning
confidence: 99%